Rural Parent Support of Child Health Behavior in the Home Environment: A Qualitative Study on an American Indian Reservation - Maja Pedersen MS; Blakely Brown PhD; Kari Harris PhD; Sonja France; Mike Tryon MS; Aric Cooksley BA (SAGE Publishing, 2019)
Background . Obesity rates are disproportionately high among rural and American Indian (AI) children. Health behaviors contributing to child obesity are influenced by parents at home. Engaging parents remains a challenge, particularly among low-income and ethnic minority families. Aims . The aim of this study was to learn how AI parents living on a rural AI reservation support and engage with their children's nutrition and physical activity behaviors at home. Methods . Parents with children ages 6 to 12 years living on one, rural AI reservation participated. Focus groups and interviews were conducted, using a 14-question moderator's guide. A systematic, iterative content analysis was applied to the transcripts. Results . Twenty-five parents (52% AI or Alaska Native) participated in 3 focus groups (n = 17) and interviews (n = 8). Themes related to enhancers included role modeling and whole family and child-initiated activities. Barriers included resources, child safety concerns, driving distances, and competing family priorities. Themes related to strategies for change included opportunities for peer learning from other local families, creating fun, program support for all supplies and incentives, and incorporation of storytelling and multicultural activities. Discussion . This study advances knowledge to promote parental engagement with child health behavior in the home, including unique themes of inclusiveness, culture-focused, and intergenerational activities. Conclusion . Results may inform interventions seeking to engage parents living in rural and AI reservation communities in home-based child behavior change efforts.